TARO CATTLE AURICLE MORFOMETRY IN TARO VILLAGE, TEGALLALANG DISTRICT, GIANYAR REGENCY, BALI - Lestari, Silvia Dwi; Heryani, Luh Gde Sri Surya; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2022)
In contrast to Bali cattle, which have known characterization of both body sizes and genetics, the Taro white cattle not many people know the phenotypic and genotypic characterization. The ear is one of the important organs of the body to determine the morphometric characterization of cattle. The ear is an important organ that functions to maintain balance, which is related to other organs such as the eyes, joints, muscles, and skin. This research is done to determine the morphometry of white taro cattle’s auricle in Taro village, Tegallalang District, Gianyar Regency, Bali, Indonesia. The amount of samples used is 26 taro cattle (> 3 years old). Measuring tape with cm as its unit is used to measure the auricle. The data collected includes length and width analyzed quantitatively. To test the differences between males and females, a T-test (Independent T-test) was used, the analytical procedure using the SPSS program was used. The measurement of the auricle of the male and female taro white cattle obtained the average length and width of the bulls (22.833 cm and 3.8883 cm) while in females (21.785 and 3.5771 cm) the P value < 0.01 (P = 0.00) means that there is a very significant difference between the average length and width of the ear auricles of male and female white cattle. Longer auricles can adapt more easily to hot conditions. The standard deviation value is smaller than the average value which indicates the data is acceptable or homogeneous.